2021
DOI: 10.1001/jamapsychiatry.2021.0150
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Suicide Attempt in Patients With Recent Diagnosis of Mild Cognitive Impairment or Dementia

Abstract: IMPORTANCELittle is known about the association between mild cognitive impairment (MCI) and suicide. Most studies have focused on dementia and suicidal behavior, with inconsistent results.OBJECTIVES To examine the association between diagnoses of MCI and dementia and suicide attempt and explore potential psychiatric moderators and to assess whether the association differs based on recency of diagnosis. DESIGN, SETTING, AND PARTICIPANTS This nationwide cohort study integrated 5 national databases from the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 54 publications
0
31
0
1
Order By: Relevance
“…Individual-level risk factors for firearm suicide include alcohol and substance misuse, dementia or other cognitive impairment, prior suicide attempt, chronic pain, and serious and poorly controlled mental illness [3,4,[35][36][37][38][39][40][41][42][43][44]. As many as 10 % of American adults self-report both patterns of impulsive, angry behaviors and access to firearms [45].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Individual-level risk factors for firearm suicide include alcohol and substance misuse, dementia or other cognitive impairment, prior suicide attempt, chronic pain, and serious and poorly controlled mental illness [3,4,[35][36][37][38][39][40][41][42][43][44]. As many as 10 % of American adults self-report both patterns of impulsive, angry behaviors and access to firearms [45].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
“…Firearm access poses risk for people with dementia: in the USA, 60 % of persons with dementia live in a home with a firearm, and firearms are the most common means of suicide among persons with dementia [49,50]. Research has found that risk of suicide may be especially elevated in the period after an older adult receives a dementia or mild cognitive impairment diagnosis [43]. Talking with caregivers of patients with dementia about the risk of firearms remains rare [51], and experts suggest that conversations about firearms and dementia should parallel those about driving and dementia [52].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
“…As performed previously by our group, we derived MCI and dementia diagnoses using ICD-9/10 codes in NPCD and CMS claims data 13,14 (Table S1). Medical record data assessed demographics (i.e., age, sex, race/ethnicity);…”
Section: Methodsmentioning
confidence: 99%
“…The overall adjusted incidence risk ratio was 0.8 (95% CI, 0.7-0.9); during the first month after diagnosis it was 3.0 (95% CI, 1.9-4.6; P < .001) (Erlangsen et al, 2020). Increased risk of suicide attempt has also been reported in patients with a recent diagnosis of dementia and mild cognitive impairment (Günak et al, 2021).…”
Section: Introductionmentioning
confidence: 93%